Reading fluency intervention dosage: A novel meta-analysis and research synthesis. (June 2022) - Maki, Kathrin E.; Hammerschmidt-Snidarich, Stephanie
Abstract: Reading fluency is a fundamental component of reading proficiency, and yet, it is a common area of need for students demonstrating reading difficulties. In response, reading fluency interventions have been researched and implemented relatively extensively, but how much intervention is needed to affect reading fluency growth is not clear. The purpose of this study was to meta-analyze and synthesize the research base regarding targeted reading fluency interventions for kindergarten through 12th grade students and to examine how intervention dosage is conceptualized and measured in these interventions. Thirty-three articles met the study inclusion criteria, and overall effects of reading fluency interventions were moderate (effect size = 0.46, 95% CI [0.23, 0.68], p  < .001), with study design (group design ES = 0.41, single case design ES = 0.75) and study rigor moderating study effects (group design met standards ES = 0.57, group design did not meet standards ES = 0.34, single case design met standards ES = 0.79, single case design did not meet standards ES = 0.57). Most studies conceptualized and reported intervention dosage as the amount of time spent in intervention with intervention duration impacting total intervention growth. Implications for practice and research are discussed, particularly the need for additional research examining proximal measurement of intervention dosage in an effort to best understand how opportunities to practice impact reading fluency growth.